2021
DOI: 10.1016/j.infpip.2021.100123
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention in endoscopy practice: comparative evaluation of re-usable vs single-use endoscopic valves

Abstract: Summary Re-usable air/water and suction valves used in endoscopes often demonstrate risk of infection. To the authors' knowledge, the safety and efficacy of re-usable and single-use valves have not been compared to date. As such, a laboratory investigation was undertaken to compare the safety and efficacy of re-usable and single-use valves at 11 Italian endoscopy sites. Safety was evaluated by analysing the rinse liquid of reprocessed re-usable valves ready for use, and efficacy was assessed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…These are particularly relevant when it comes to intra-procedural carbon reduction. Because of the potential risk of cross-contamination, 28,29 endoscopic accessories are primarily single-use nowadays. Our study showed that reusing instruments and reducing endoscopic accessories are highly controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These are particularly relevant when it comes to intra-procedural carbon reduction. Because of the potential risk of cross-contamination, 28,29 endoscopic accessories are primarily single-use nowadays. Our study showed that reusing instruments and reducing endoscopic accessories are highly controversial.…”
Section: Discussionmentioning
confidence: 99%
“…É hipotetizado que Rothia spp. tem maior perfil de resistência a antibióticos e uma maior virulência quando consorciada em biofilmes 39 . Biolfilmes monoespécies e polimicrobianos contendo Rothia spp.…”
Section: Discussionunclassified
“…Também pesquisadores relatam que R. dentocariosa foi encontrada em pacientes com endocardite infecciosa e que não apresentavam infeções bucais aparentes, não sendo possível determinar a causa da infecção por Rothia spp. 39 .…”
Section: Discussionunclassified
“…These include biopsy forceps, biopsy containers, cold and hot snare catheters, snare diathermy pads and others. The risk of cross-contamination and patient safety concerns have led to the almost ubiquitous use of single-use accessories,120–122 but such disposable equipment is likely to increase net waste 101. To mitigate the environmental impact of disposable accessories, training endoscopists and staff in preventing excess and inadvertent use of accessories by appropriate planning preprocedure is recommended 123.…”
Section: Methodsmentioning
confidence: 99%